Sistem Whistleblowing dalam Penanganan Kasus Penyelewengan Etika - Ary Satyasmoko; Tjiptohadi Sawarjuwono (ITB AAS INDONESIA, 2021)
This study aims to explain the whistleblowng system in handling ethics wrongdoings. Ethics wrongdoings happened because of the absence of internal controls such as whistleblowing system. Whistleblowing system excourages and helps whistleblower in reporting wrongdoings related to ethics. Hence it is necessary to apply some elements of whistleblowing system to a company. Some elements include the implementation statement, reporting range, procedure, whistleblower protection, mechanism of whistleblowing system, and effectivity will be analyzed. Therefore, the implication about the verdict of whistleblowing system will also be explained. These elements will be used to examine three companies’whistleblowing system. These companies are PT. Pertamina, PT. Telkom and PT. BCA from 2016 to 2019 using library research method.